Designing a Google Voice-Based Solar Panel Cleaner Control System - Tessal, Dasrinal; Marzal, Jefri; Triantini, Dewi; Wirasapta , Andicho Haryus; Fikri , Muhammad Khalis; Saputra , Angga Riyan Trio; Mishi , Salmuna Sajjad (DPTE FT UNY, 2025)
Current solar panel maintenance often involves manual, rooftop fieldwork, which introduces significant fall-from-height risks and occupational hazards. To address this, this research investigates the integration of the Internet of Things (IoT) to streamline and enhance operational efficiency. The goal is to develop an IoT-enabled solution for user-driven routine maintenance that can significantly mitigate occupational hazards and reduce maintenance duration. This system is designed to optimize the long-term energy yield of solar panels by preventing the typical efficiency decline caused by neglected upkeep. The study employs a prototype development method (literature review, construction model design, and control system development). The final system leverages common consumer-grade terminal devices (smartphones, laptops) to provide a ubiquitous, real-time control interface, allowing users to manage the system remotely via a stable network connection.